ALGORITMA PENGATURAN KINEMATIKA ROBOT REDUNDANT UNTUK MENGHINDARI TERJADINYA TUMBUKAN BERDASARKAN SKEMA PRIORITAS TUGAS - GEDE SANTI ASTAWA; G.K. GANDHIADI (Jurnal Matematika, 2007)
A redundant manipulator has more degree of freedom than minimal needed to do its job. Inthis condition the manipulator can easily do the job, and can say become not optimal. To makethe manipulator more optimal, we try to add some obstacles that must be avoided by themanipulator. in calculation process we use inverse kinematics method in task priority scheme.From the simulation result, it is looked that by adding some jobs do not annoy the main job ofmanipulator, and those prove that the priority of the job can help manipulator do that job moreoptimal.